2023
DOI: 10.3390/ijms24098379
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Regulates the Profibrotic Activity of Fibroblasts in In Vitro Replica Settings of Myocardial Infarction

Abstract: Extracellular collagen remodeling is one of the central mechanisms responsible for the structural and compositional coherence of myocardium in patients undergoing myocardial infarction (MI). Activated primary cardiac fibroblasts following myocardial infarction are extensively investigated to establish anti-fibrotic therapies to improve left ventricular remodeling. To systematically assess vitamin C functions as a potential modulator involved in collagen fibrillogenesis in an in vitro model mimicking heart tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…At specific concentration levels, ROS has a detrimental or beneficial role in cell function (levels see Section 3.1 ) [ 79 ]. Oxidative stress is one of the main contributors to generating uncontrollably large amounts of ROS.…”
Section: The Role Of Vitamin C In Cardiovascular Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At specific concentration levels, ROS has a detrimental or beneficial role in cell function (levels see Section 3.1 ) [ 79 ]. Oxidative stress is one of the main contributors to generating uncontrollably large amounts of ROS.…”
Section: The Role Of Vitamin C In Cardiovascular Pathologiesmentioning
confidence: 99%
“…Although the mechanisms for reducing the cardiovascular risk remain unclear, the role of vitamin C in scavenging ROS [ 178 ], enhancing NO production [ 179 ], and its potential benefits for microperfusion [ 177 ], myocardial protection [ 79 ], and hemodynamic stability [ 180 ]—especially in critically ill patients [ 181 ]—is increasingly recognized.…”
Section: The Role Of Vitamin C In Cardiovascular Pathologiesmentioning
confidence: 99%
“…For example, in vitro evidence has shown that vitamin C, such as from citrus fruits and bell peppers, can increase nitric oxide bioavailability, which can induce vasodilation and promote the integrity of the endothelium and hence lower blood pressure [49]. Vitamin C may also protect cell constituents against oxidative stress and aid in the synthesis of several relevant biomolecules via acting as an enzymatic cofactor, thus playing a pivotal role in several processes involved in the pathogenesis of CVD [50,51]. These antioxidant properties are notable as reducing oxidative stress is believed to be a key factor in the prevention of cardiovascular pathology [52].…”
Section: Findings In Relation To the Existing Literaturementioning
confidence: 99%
“…In an elegant experimental study, Yichen Xu et al [5] focused on the topic of connective tissue changes after myocardial infarction, similar to the study by Schumacher et al [4]; however, they went further and investigated the effect of vitamin C at various doses in a mice model. Concentrations from 0 to 50 ug/mL (0, 10, 20, 30, 40, 50 ug/mL) were used.…”
mentioning
confidence: 99%